Faktor yang Mempengaruhi Kinerja Layanan Jalan Tol Bakauheni-Terbanggi Besar (Bakter) - Jamaludin, Jamaludin; Dewanti, Dewanti; Priyanto, Sigit (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2023)
The Bakter Toll Road, which is managed by PT. Hutama Karya is a freeway that connects traffic movements between cities and provinces. The Bakter Toll Road has been operating for more than 3 years. However, so far no research has been conducted on whether the Bakter toll road has met the expectations of its users. Based on this, it is necessary to conduct a study on the analysis of road service satisfaction related to the services it provides. The data used are in the form of questionnaire data, observations of available toll road facilities, and data from related agencies. Sampling for the questionnaire used purposive sampling to 306 respondents online and offline. Based on the results of the analysis using the factor analysis method regarding the factors that influence the service performance of the Bakauheni-Terbanggi Besar toll road, it is known that there are 3 influencing factors, namely the facility factor 9.83 (44.68%), service factor 2.71 (12.32%) ) and a traffic flow performance factor of 1.42 (6.43%).